التربية الإعلامية الرقمية الأبعاد والضوابط (Journal of Academic Research, 2024)
The concept of digital media education is considered is one of the concepts that have increased in importance recently. The world today relies heavily on digital media and social networking sites and it has become an integral part of the life of every individual in society, and has entered into many fields such as education, health, commerce, psychology, sociology and medicine. Therefore, there were many negative and positive impacts on the individual and society, which led to the emergence of digital societies whose dependence on the Internet and the multiple sites it carries within it became clear. It is worth noting that it transports the individual from a real reality to an intangible virtual world, but exposure for long hours may lead to a change in his attitudes and behaviours, which may be for the better or for the worse. From here, interest began in digital media education, which determines how digital media is dealt with, which requires learning skills and learning the foundations and principles of reading media messages, analyzing them, subjecting them to criticism and change, processing texts by deconstructing them and studying them to find out the true meaning behind presenting these media contents, and then reproducing and broadcasting it